Two-dimensional Materials for Energy Storage and Harvesting - LIANG, MEIYING JENNY (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2020)
Energy storage and harvesting have become a global concern due to the ever-increasing demand for energy and upcoming depletion of natural resources. As a family of Van der Waals layered crystals, metal chalcogenides (MCs) and transition metal chalcogenides (TMDs) possess unique electronic and photonic properties, enabling high-performance electronic devices for broad applications. However, the potential application of MCs and TMDs in energy devices remains relatively unexplored, partially due to their challenges in exfoliation as well as poor electrical conductivity. This PhD thesis mainly discussed the preparation and energy application of 2D MCs and TMDs materials. The liquid phase exfoliation (LPE) method was demonstrated as a viable method to give large-scale 2D MCs and TMDs nanosheets at low cost, enabling efficient solution processing of thin films, composites and devices. The resultant 2D MCs and TMDs nanosheets were utilized to fabricate high-performance lithium-ion batteries (LiBs) and solar cells (SCs). Four different 2D MCs (i.e., GaS, gallium (II) selenide [GaSe], gallium (II) telluride [GaTe] and indium (II) selenide [InSe]) were percolated in single-wall carbon nanotube (SWCNT) networks to obtain the conductive and flexible anode for LiBs. Based on the general comparison of them, we found the 2D InSe-SWCNT composite anode exhibits a superior electrochemical performance (including high capacity and excellent rate capability). Importantly, the capacity per InSe of 2D InSe-SWCNT composite anode increases over prolonged cycling up to 1224 mAh g-1 from 520 mAh g-1 (after 254 cycles, at 500 mA g-1), which is believed to largely relate with the reversible alloy reaction, as confirmed by the operando X-ray diffraction results. By combining the density functional theory (DFT) calculations and post-cycling scanning electron microscope (SEM) images, we reveal that the in situ formed In particles gradually reduce their domain size, forming nanoclusters upon cycling which are capable to accommodate four Li+ instead of one per atomic In, and leading to extra capacity as increasing the cycling numbers. Such a new "nanocluster-alloying" Li storage mechanism may inspire new architectures or methods to prepare anode materials for excellent performance LiBs. Besides, 2D TMDs (e.g. MoS2, MoSe2, etc.) were tried as 1) absorber, 2) hole transport layer (HTL), and 3) buffer layer of solar cells. Through this study, we found that 2D TMDs obtained via LPE method is not suitable to be an active layer of solar cells due to the limitation of reducing the 2D TMDs nanosheets thickness. However, they have potential to be used as a HTL or a buffer layer of perovskite solar cells (PSCs) to reduce the cost and improve the stability of the device. There is still a large space to improve the PV performance of solar cells with 2D TMDs nanosheets, and this practical built the foundation for further research.
APPROVED
Keywords: two-dimensional metal chalcogenides and transition metal chalcogenides; liquid phase exfoliation; lithium ion battery; solar cell